2018
DOI: 10.1126/science.aap8074
|View full text |Cite
|
Sign up to set email alerts
|

Factoring stream turbulence into global assessments of nitrogen pollution

Abstract: The discharge of excess nitrogen to streams and rivers poses an existential threat to both humans and ecosystems. A seminal study of headwater streams across the United States concluded that in-stream removal of nitrate is controlled primarily by stream chemistry and biology. Reanalysis of these data reveals that stream turbulence (in particular, turbulent mass transfer across the concentration boundary layer) imposes a previously unrecognized upper limit on the rate at which nitrate is removed from streams. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 28 publications
2
80
0
Order By: Relevance
“…of a = 0.17 and b = 2/3 Grant et al (2018). recently extended O'Connor and Hondo's laboratory results to the field, showing that the SRT mass transfer coefficient k m sets an upper bound on measured rates of nitrate removal by assimilation and denitrification in 69 headwater streams across the United States (included as part of the second Lotic Intersite Nitrogen eXperiment;Mulholland et al, 2008).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…of a = 0.17 and b = 2/3 Grant et al (2018). recently extended O'Connor and Hondo's laboratory results to the field, showing that the SRT mass transfer coefficient k m sets an upper bound on measured rates of nitrate removal by assimilation and denitrification in 69 headwater streams across the United States (included as part of the second Lotic Intersite Nitrogen eXperiment;Mulholland et al, 2008).…”
mentioning
confidence: 87%
“…For example, O'Connor and Hondzo (2008) reported that SRT correctly predicts the flux of oxygen from the bulk stream to organic‐rich sediments given a choice of constants in equation of a = 0.17 and b = 2/3. Grant et al () recently extended O'Connor and Hondo's laboratory results to the field, showing that the SRT mass transfer coefficient k m sets an upper bound on measured rates of nitrate removal by assimilation and denitrification in 69 headwater streams across the United States (included as part of the second Lotic Intersite Nitrogen eXperiment; Mulholland et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above (2.1), hydrostatic and hydrodynamic heads along uneven streambeds have long been known as drivers of hyporheic flow [1,27,45] that pose a hydromechanical (transport) limitation on nutrient biogeochemistry [39,218,219] and impact the regional groundwater discharge patterns [41]. However, there is still uncertainty connected to the importance of these drivers over a wide range of temporal and spatial scales [220,221].…”
Section: Scale Transferabilitymentioning
confidence: 99%
“…Many factors have been shown to control sediment NO 3 − reduction rates, including NO 3 − , C, and O 2 concentrations, and gene abundance (e.g., see Lisa et al, 2015;Pina-Ochoa & Alvarez-Cobelas, 2006). While the dynamics of water movement have been recognized as a controlling factor for N attenuation in hyporheic zones of streams and rivers (Böhlke et al, 2009;Grant et al, 2018;Harvey et al, 2013;Seitzinger et al, 2006;Zarnetske et al, 2012) and subterranean estuaries (Kroeger & Charette, 2008;Michael et al, 2005;Spiteri et al, 2008;Ueda et al, 2003), this lakebed study clearly emphasizes the importance of hydrologic transport and the associated seasonal variability on the spatial pattern of groundwater N delivery to lakes and the limiting effect of electron donor availability along upgradient groundwater flow paths.…”
Section: In Situ Controls On Nitrite and Nitrate Attenuationmentioning
confidence: 99%